The art of modelling / Yap Yin @ Yap Kee Kong - Yap, Yin
To a layman, the word "model" is associated with the photogenic models he sees in fashion magazines. Apart from being a noun, the word "model" can also be used as an adjective and a verb. As an adjective "model" implies a degree of perfection or idealization as in reference to a model home, a model student or a model husband. As a verb "to model" means to demonstrate, to reveal, to show what a thing is like. Scientific models, on the other hand, are used as a representation of any subject of enquiry such as objects, events, systems and processes. The most important function of scientific models is to enable a researcher to study how changes in the features of a model entity can affect other features or the whole entity. Hence, through manipulation of the model, the researcher can gain further insights into the problems concerning the operations of an entity. In any formal research into a process or a system scientific modelling plays a very important role in reducing cost and time. Instead of manipulating an actual object or process, its model is being manipulated. This advantag